2019
DOI: 10.48550/arxiv.1902.07826
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Certainty Equivalence is Efficient for Linear Quadratic Control

Horia Mania,
Stephen Tu,
Benjamin Recht

Abstract: We study the performance of the certainty equivalent controller on Linear Quadratic (LQ) control problems with unknown transition dynamics. We show that for both the fully and partially observed settings, the sub-optimality gap between the cost incurred by playing the certainty equivalent controller on the true system and the cost incurred by using the optimal LQ controller enjoys a fast statistical rate, scaling as the square of the parameter error. To the best of our knowledge, our result is the first sub-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(47 citation statements)
references
References 19 publications
(51 reference statements)
3
44
0
Order By: Relevance
“…This way of designing the control policy is also known as the certainty equivalence approach (e.g., [4]). Specifically, the authors in [10,25] provided an online algorithm for the LQR problem with unknown system matrices and showed that the regret of the algorithm is Õ( √ N ), where N is the number of time steps in the LQR problem and Õ(•) hides logarithmic factors in N . Note that the authors in [1,11,10,25] considered the infinite horizon LQR setting.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…This way of designing the control policy is also known as the certainty equivalence approach (e.g., [4]). Specifically, the authors in [10,25] provided an online algorithm for the LQR problem with unknown system matrices and showed that the regret of the algorithm is Õ( √ N ), where N is the number of time steps in the LQR problem and Õ(•) hides logarithmic factors in N . Note that the authors in [1,11,10,25] considered the infinite horizon LQR setting.…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, the authors in [10,25] provided an online algorithm for the LQR problem with unknown system matrices and showed that the regret of the algorithm is Õ( √ N ), where N is the number of time steps in the LQR problem and Õ(•) hides logarithmic factors in N . Note that the authors in [1,11,10,25] considered the infinite horizon LQR setting. We extend the analyses and results in [25] to the finite horizon LQR setting when solving the problem considered in this paper.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations